RAMADAN DAN PROMOSIONAL: STRATEGI KOMUNIKASI PEMASARAN PT UNILEVER INDONESIA TBK - Pertiwi, Amalia; Jusnita, Raden Ayu Erni; Maela, Nurannafi Farni Syam (Jurnal Komunikasi Profesional, 2019)
The purpose of this research is to know marketing communication strategy conducted by PT. Unilever Indonesia Tbk. using media webpage in increasing sales especially in the month of Ramadan. This research uses descriptive research type using qualitative method. Data collection techniques used in this study are literature study and field study of field observation (field obersvation) and depth interviews (depth interview) on the parties who play an important role in PT. Unilever Indonesia Tbk. Based on the results of research, found that marketing communication strategy conducted by PT. Unilever Indonesia through media webpage is known to be quite effective in increasing consumer buying interest and increasing sales during the session. By using marketing mix on E-marketing Mix that is, Product (product), Price (price), place (place).Keywords: Marketing Communication, Webpage, PT. Unilever Indonesia Tbk